Fair Value and Audit Fees: The Moderating Effect of Auditor Industry Specialization in IDX-Listed Financial Firms - Rahmawati, Aulia; Ahzar, Fahri Ali; Wardhani, Marita Kusuma; Aligarh, Frank (Manunggal Halim Jaya, 2026)
This research examines the influence of fair value measurement on audit fees and the moderating role of auditor industry specialization. The study covers all firms listed on the Indonesia Stock Exchange, from which 955 entities were screened, and 45 firms meeting the criteria were selected using purposive sampling. A total of 135 firm-year observations were analyzed using the Random Effects Model (REM) in EViews. The findings indicate that fair value measurement is associated with higher audit fees due to greater estimation uncertainty and more intensive audit procedures, especially for complex valuation levels. Auditor industry specialization, measured through both market-based and portfolio-based indicators, also plays a significant role and strengthens the effect of fair value measurement on audit fees. The study highlights that specialized auditors respond differently depending on their experience and portfolio, intensifying the impact of fair value practices. Addressing limited evidence from emerging markets, this research clarifies how valuation complexity interacts with auditor expertise in shaping audit pricing. Practical implications arise for auditors, firms, and regulators in planning and transparency.